Success factors and future trends in mass customization - Modrák, Vladimír; Soltysova, Zuzana; Stadnicka, Dorota (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2018)
At first, this paper focuses on the market-oriented challenges associated with the necessity to continuously update product offers in order to serve today’s markets and remain competitive. Subsequently, some success factors for mass customization (MC) are identified in this study. Then, a generic model of a mass customization system for manufacturing companies is proposed. Additionally, chosen problems concerning the mass customization implementation are highlighted. Finally, the work provides a summary of the features and trends of MC and offers new views on the subject. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)